2006
DOI: 10.1007/s11430-006-0431-4
|View full text |Cite
|
Sign up to set email alerts
|

Temporal-spatial variations of euphotic depth of typical lake regions in Lake Taihu and its ecological environmental significance

Abstract: By using the data of underwater irradiance measured in the different lake regions of Lake Taihu during 1998-2004 and total suspended solids (TSS), wind speeds of the total 13 stations in typical lake regions during 1993-2003, this paper analyzes the factors of influencing on PAR (photosynthetically available radiation) attenuation, euphotic depth, and presents the temporal and spatial variations of euphotic depth of typical lake regions in Lake Taihu, and the spectral distributions of euphotic depth at station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
3
22
1
1
Order By: Relevance
“…The GIs of all the sample points were calculated and the results (Table 2) showed that the highest GIs were obtained by comparing between TSM and Kd(PAR). These results indicated that TSM had a higher contribution to Kd(PAR) than Chl-a and CDOM, which is consistent with previous studies in Lake Taihu in China [7,12] and UK marine waters [10]. Furthermore, in order to assess the difference of the relationships across various waters, lakes with more than 10 sampling points were also selected to calculate GIs individually.…”
Section: Grey Incidences Between Kd(par) and Oacssupporting
confidence: 88%
See 3 more Smart Citations
“…The GIs of all the sample points were calculated and the results (Table 2) showed that the highest GIs were obtained by comparing between TSM and Kd(PAR). These results indicated that TSM had a higher contribution to Kd(PAR) than Chl-a and CDOM, which is consistent with previous studies in Lake Taihu in China [7,12] and UK marine waters [10]. Furthermore, in order to assess the difference of the relationships across various waters, lakes with more than 10 sampling points were also selected to calculate GIs individually.…”
Section: Grey Incidences Between Kd(par) and Oacssupporting
confidence: 88%
“…The average of the data can eliminate the error to some extent and result in a stable performance. The slope of the linear model between K d (PAR) and TSM in the current study was slightly higher than results in [7] (slope = 0.0626, intercept = 1.6068) and [12] (slope = 0.0563, intercept = 1.52). Considered that our research covered a larger number of lakes than those earlier studies, such a difference was acceptable.…”
Section: K D (Par) Model Calibration and Validationcontrasting
confidence: 85%
See 2 more Smart Citations
“…and pH were measured in situ with Hanna Ò HI98129 Combo tester. Additional physical and chemical characteristics ( Zhang et al (2006). The samples for the analyses of the water chemistry were also collected with 1L Ruttner sampler.…”
Section: Sampling and Analytical Workmentioning
confidence: 99%